Karakteristik Anak yang Rawan Terjerat Eksploitasi Seksual Komersial: Studi Kasus di Surabaya Bekerjasama dengan LSM Abdi Asih Surabaya - Eli Inayanti; Zahroh Shaluhiyah; Bagoes Widjanarko (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTData from ECPAT (End Child Prostitution, Child Pornography and the Trafficking of Children for Sexual Purpose), an estimated 40,000 to 70,000 child victims of sexual exploitation throughout Indonesia, expected 21,000 involved in prostitution on the Island of Java. Abdi Asih NGOs as NGOs and child protection and oldest woman in Surabaya shows child victims of CSEC in 2013 from 28 cases of commercial child sexual exploitation, child prostitution topped with 23 (82%) cases, the youngest 12 years and oldest 18 years. Underlying factors also very complex, such as economy factors 19 (67%), datting and peer pressure 6 (21%), lack of conrol and parental love 2 (7%), lifestyle 1 (3,5%). Eksploiter is not only by strangers but more done by people known to the victim as his girlfriend and neighbors. Children are the group that many touted to be the victim of sexual exploitation as helpless. Child commersial eksploitasion is very dangerous, because such sex usually unprotected, children are rarely in a position to negotiate safer sex and therefore carry a greater risk of becoming infected with HIV or other STD. Children are olso at risk to damage the long-term social and psychological.Keyword : child, exploitation,sexual, commercial